3 sin^2x-cosx+1=0
по формуле sin^2(x) + cos^2(x) = 1
3 sin^2(x) = 3 - 3 cos^2(x)
3 - 3cos^2(x) - cos(x)+1=0
3cos^2(x) + cos(x) - 4 = 0
Дальше можно через дескриминант или по теореме Виетта
Я пойду первым способом
Заменим cos(x)=t
3t + t - 4=0
![t=\frac{1+-\sqrt{1+48}}{6}=\frac{1+-7}{6} t=\frac{1+-\sqrt{1+48}}{6}=\frac{1+-7}{6}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B1%2B-%5Csqrt%7B1%2B48%7D%7D%7B6%7D%3D%5Cfrac%7B1%2B-7%7D%7B6%7D)
=> t=4/3 и t=1
=> cos(x) = 4/3 - что не возможно и cos(x)=1
=> x=0
Вроде бы так)
Удачи)